Effects of Relative Molecular Weight Distribution and Isoelectric Point on the Swelling Behavior of Gelatin Films - Ji, Fangqi; Zhou, Wei; Zhang, Ze; Zhang, Bing (Frontiers in Chemistry, 2022)
The swelling behavior of gelatin films with different extraction processes are investigated. The results showed that the swelling ratio of the gelatin film extracted by alkaline hydrolysis of collagen (type-B) in a range of pH environments was higher than the one extracted by enzymatic hydrolysis collagen (type-E). In the drug releasing simulation, type-B gelatin capsules also showed a faster collapse rate than type-E gelatin capsules. Based on analyzing relative molecular weight distribution of type-B and type-E gelatins, the more widely distributed relative molecular weight is the key attribution for enabling easier diffusion of water molecules inside the porous channels of peptide chains. Furthermore, with the pH of solution environment far from the isoelectric point (pI) of gelatin films, the swelling ratios were found to increase remarkably, which is due to electrostatic repulsion expanding the pore size of peptide chains. Finally, the addition of SO42- in gelatin film was performed to confirm the dominant effect of component compared to pI on swelling behavior of gelatin films.